Telomere Length in Valve Tissue Is Shorter in Individuals With Aortic Stenosis and in Calcified Valve Areas - Saraieva, Ilona; Benetos, Athanase; Labat, Carlos; Franco-Cereceda, Anders; Bäck, Magnus; Toupance, Simon (Frontiers in Cell and Developmental Biology, 2021)
Background Short telomere length (TL) is associated with age-related diseases, in particular cardiovascular diseases. However, whether the onset and course of aortic stenosis (AS) is linked to TL in aortic valves remains unknown. Objectives To assess telomere dynamics (TL and telomerase activity) in aortic valves and the possible implication of TL in onset and course of AS. Methods DNA was extracted from aortic valves obtained from 55 patients (78.2% men; age, 37–79 years), who had undergone replacement surgery due to AS (AS group, n = 32), aortic valve regurgitation and aortic dilation (Non-AS group, n = 23). TL was measured by telomere restriction fragment analysis (TRF) in calcified and non-calcified aortic valve areas. Telomerase activity was evaluated using telomerase repeat amplification protocol (TRAP) in protein extracts from non-calcified and calcified areas of valves obtained from 4 additional patients (50% men; age, 27–70 years). Results TL was shorter in calcified aortic valve areas in comparison to non-calcified areas (n = 31, 8.58 ± 0.73 kb vs. 8.12 ± 0.75 kb, p < 0.0001), whereas telomerase activity was not detected in any of those areas. Moreover, patients from AS group displayed shorter telomeres in non-calcified areas than those from the Non-AS group (8.40 ± 0.64 kb vs. 8.85 ± 0.65, p = 0.01). Conclusions Short telomeres in aortic valves may participate in the development of AS, while concurrently the calcification process seems to promote further local decrease of TL in calcified areas of valves.